Analysis of Factors That Influence Snack Food Selection Behavior in High School Students - Ulfaini Safitriani; Dyah Suryani; Surahma Asti Mulasari (Universitas Ibn Khaldun Bogor, 2023)
BPOM findings from 2006-2010 showed that as many as 48% of school children's snacks did not meet food safety requirements because they contained dangerous chemicals. Snacking behaviour is influenced by several factors, including knowledge, attitudes, peers, and family involvement in getting used to breakfast or providing food from home to be taken to school. This research analyses the factors influencing snack food selection behaviour among high school students. The method in this research is to examine literature reviews with the study sources used coming from published journals in Indonesia and having an ISSN relating to research. As a result of research from 124 articles reviewed, five reports were finally obtained; it was found that there was an influence of knowledge, attitudes, health education and the role of authoritarianism on high school children's snack choices. Shows that knowledge, attitudes, health education and authoritarian roles influence food choices in children or adolescents; there are three factors, namely: (1) predisposing factors, namely factors that facilitate and underlie the occurrence of specific behaviour; (2) supporting factors that enable particular behaviour to occur, such as information media, health service infrastructure, and (3) reinforcing factors are factors that strengthen the occurrence of specific behaviour (the role of parents and the role of teachers).